2014
DOI: 10.2478/jppr-2014-0041
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Bt-Transgenic Cotton and the Whitefly’s Parasitoid, Encarsia Formosa (Hymenoptera: Aphelinidae)

Abstract: Transgenic Bt cotton developed against lepidopteran pests may not be compatible with parasitoid of secondary pests such as Bemisia tabaci which attack many plants such as cotton. In this study, the effects of Bt cotton on the demographic parameters of Encarsia formosa, parasitoid of B. tabaci were assessed. The data were analysed using the age specific, two-sex life table parameters. The results indicated that pre-adult developmental time, the total preoviposition period (TPOP) and the adult preoviposition per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
1
1
3
Order By: Relevance
“…The values corresponding to the periods egg to larva and pre-imago of this study differ from those found by Azimi et al (2014) for Encarsia formosa, and Pessoa et al (2016) for Encarsia desantisi (Hymenoptera: Aphelinidae) in non-BT cotton. Thus, researchers have shown that species from the genus Encarsia may reduce or extend its life cycle in function of the host plant where the whitefly developed.…”
Section: Development Of E Hispida On Bemisia Tabaci Biotype B In Cottoncontrasting
confidence: 99%
“…The values corresponding to the periods egg to larva and pre-imago of this study differ from those found by Azimi et al (2014) for Encarsia formosa, and Pessoa et al (2016) for Encarsia desantisi (Hymenoptera: Aphelinidae) in non-BT cotton. Thus, researchers have shown that species from the genus Encarsia may reduce or extend its life cycle in function of the host plant where the whitefly developed.…”
Section: Development Of E Hispida On Bemisia Tabaci Biotype B In Cottoncontrasting
confidence: 99%
“…Pengaruh langsung dari tanaman transgenik apabila musuh alami memakan nektar dari tanaman transgenik. Sedangkan pengaruh tidak langsung dari tanaman transgenik apabila musuh alami memparasit atau memakan hama yang hidup pada tanaman transgenik (Arpaia et al dalam Azimi et al, 2014). Parasitoid Encarsia formosa tumbuh lambat pada kapas Bt, sehingga pertumbuhan dan perkembangannya lebih lambat dibandingkan parasitoid pada kapas non Bt (Azimi et al, 2014).…”
Section: Pengaruh Tanaman Transgenik Terhadap Organisme Non Target Pe...unclassified
“…Sedangkan pengaruh tidak langsung dari tanaman transgenik apabila musuh alami memparasit atau memakan hama yang hidup pada tanaman transgenik (Arpaia et al dalam Azimi et al, 2014). Parasitoid Encarsia formosa tumbuh lambat pada kapas Bt, sehingga pertumbuhan dan perkembangannya lebih lambat dibandingkan parasitoid pada kapas non Bt (Azimi et al, 2014). Pada kajian yang dilakukan selama 4 tahun di lima lokasi di Wisconsin, diperoleh data bahwa populasi predator rata-rata 63,8% lebih rendah di lahan-lahan yang ditanami kentang non-Bt yang pengendalian hamanya dengan menggunakan pestisida dibanding dengan lahan-lahan yang ditanami kentang Bt transgenik, sedangkan pada lahan-lahan yang disemprot pestisida 58,4% lebih rendah dibandingkan dengan populasi parasitoid di areal pertanaman transgenik Bt (Hoy et al, 1998).…”
Section: Pengaruh Tanaman Transgenik Terhadap Organisme Non Target Pe...unclassified
See 1 more Smart Citation
“…Some studies also reported that Bt-cotton plants provide substantial economic benefits and reduce the use of harmful insecticides [6,7] . The secondary pests such as aphids, mirid bugs and whiteflies are not susceptible to Bt-cotton plants and they directly benefit from reduced application of chemical insecticides [8][9][10][11][12] . Specifically, the mirid bugs (Heteroptera: Miridae) have shown tendency to produce outbreaks and were suggested to be considered as a primary target for development forecasting and management strategies in Btcotton fields in China [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%